PENTINGNYA PERAN MASYARAKAT DALAM MENDUKUNG PROGRAM KERJA DESA DI DESA DUMATI KECAMATAN TELAGA BIRU - Yolanda Ngabito; Sulisnawati Mato; Nur Febrianti (Journal of Hulonthalo Service Society (JHSS), 2022)
Dumati Village, located in Telaga Biru District, has various work programs aimed at improving community welfare. This article discusses the importance of the active role of the community in supporting these programs. The community service methods used include a participatory approach, interviews, and focus group discussions. The results show that community participation has a significant effect on the success of village programs, especially in terms of economic empowerment and infrastructure development. This article recommends strategies to strengthen collaboration between the village government and the community.